PEMBUATAN SABUN PADAT TRANSPARAN MENGGUNAKAN MINYAK KELAPA SAWIT (Palm oil) DENGAN PENAMBAHAN BAHAN AKTIF EKSTRAK TEH PUTIH (Camellia sinensis) - Widyasanti, Asri; Farddani, Chintya Listiarsi; Rohdiana, Dadan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2017)
Transparent soap is a kind of solid soap. The addition of white tea extracts could be expected to increase the advantageof transparent soap. The purpose of this research was to determine process and formulation for the making of transparent solid soap using palm oil based with addition white tea extracts and its effect to the characterictics of transparent solid soap. This reasearch was used laboratory experimental method using descriptive analysis. The treatment of this reasearch were addition of white tea extracts using concentrations 1% (w/v) with the addition of A= 0% (w/v), B=0.5% (w/v), C=1.0% (w/v), and D=1.5% (w/v). Parameters observed were organoleptic, chemical properties, antibacterial activity, hardness, and stability of foam. Organoleptic test results showed that panelists prefer soap treatment B with a percentage of 36.67%. The chemical properties of this soap was in accordance with SNI solid soap No.06-3532-1994, except amount of fatty acids. The value of water content and evaporated substance was 12.17%, the content of free alkali was 0.101%, the content of unsaponified fraction was 2.10%, and the amount of fatty acid was 35.67%. pH value was in accordance ASTM D 1172-95 with pH value of 10. The value of hardness was 0.0091 mm/g/s, stability of foam was 39.08%, and antibacterial activity with inhibition zone diameter was 11.28 mm. It proved that making transparent solid soap using a palm oil based and the addition of white tea extract as active ingredients could be applied by the community. Keywords:Transparant Solid Soap, Palm Oil, White Tea Extract